Student?s concepts and attitudes toward peace issues implications for peace education in the social studies curriculum - Castro, Loreta N.
The purpose of this study is to investigate the concepts and attitudes of students as a way of providing baseline information which can be helpful in the formulation of programs addressed to the promotion of peace throughout schools. The sample consisted of 692 students drawn from the three public and private largest secondary schools in Metro Manila.
This article is an abridged version of the second part of the author?s doctoral dissertation.
Keywords: Peace; High school students -- Philippines -- Manila Metropolitan Area -- Attitudes; Peace education